The Effect of Curcumin on Regression of Liver Fibrosis through Decreased Expression of Transforming Growth Factor-β1 (TGF-β1) - Supriono Supriono; Asri Nugraheni; Handono Kalim; Mudjiwijono Handaru Eko (The Prodia Education and Research Institute (PERI), 2019)
BACKGROUND: Transforming growth factor (TGF)-β1 has a pivotal role in liver fibrogenesis. Curcumin effectively prevent the progression of liver fibrosis through inhibition of TGF-β1/Sma and drosophila MAD (Smad) signaling pathway. However, the role of curcumin in the regression of liver fibrosis is still unknown. This study investigated the role of curcumin and TGF-β1 in liver fibrosis regression.METHODS: An experimental Wistar rat model included 6 treatment groups as well as positive and negative control groups. The treatment and positive control groups were injected with carbon tetrachlorid (CCl4) for 9 weeks to induce liver fibrosis. After cessation of injection, 3 of the treatment groups were given curcumin and 3 were given carboxymethylcellulose (CMC) for 2, 5 and 9 weeks, while the positive control was untreated. The negative control was injected with normal saline. TGF-β1 liver tissue levels were analyzed by ELISA, while the TGF-β1 expression in liver cells was analyzed by immunohistochemical assay. The metavir score was used to assess the degree of liver fibrosis. Values of p<0.05 were regarded as statistically significant.RESULTS: Nine weeks of CCl4 injection induced liver fibrosis (metavir F3); and significantly increased TGF-β1 levels and expression in tissues (p=0.00, p=0.021, respectively). Curcumin administration decreased levels and expression of TGF-β1 in the liver and accelerated regression of liver fibrosis. There was a significant correlation between duration of administration of curcumin with an expression of TGF-β1 in the liver tissue (r=0.87; p<0.00).CONCLUSION: Curcumin accelerates regression of liver fibrosis, likely through decreasing of TGF-β1 expression in the liver.KEYWORDS: curcumin, TGF-β1, liver fibrosis regression, CCl4, animal model